Hybrid cluster analysis of customer segmentation of sea transportation users - Cahyana, Bambang Eka (2020)
Purpose: The purpose of this study is to apply hybrid cluster analysis in classifying PT Pelindo I customers based on the level of customer satisfaction with passenger services of PT Pelindo I. Design/methodology/approach: Hybrid cluster analysis is a combination of hierarchical and nonhierarchical cluster analysis. This hybrid cluster analysis appears to optimize the advantages of hierarchical and non-hierarchical methods simultaneously to obtain optimal grouping. Hybrid cluster analysis itself has high flexibility because it can combine all hierarchical and non-hierarchical methods without any limits in the order of analysis used. Findings: The results showed that 72% of PT Pelindo I customers felt PT Pelindo I service was special, while the remaining 28% felt PT Pelindo I service was good. Originality/value: In total, 117 customers of PT Pelindo I were involved in a study using the nonprobability sampling method. DOI:  https://doi.org/10.1108/JEFAS-07-2019-0126